Diffuse Optical Spectroscopy and Imaging IX 2023
DOI: 10.1117/12.2670764
|View full text |Cite
|
Sign up to set email alerts
|

HyperProbe consortium: innovate tumour neurosurgery with innovative photonic solutions

Luca Giannoni,
Marta Marradi,
Marco Marchetti
et al.

Abstract: Recent advancements in imaging technologies (MRI, PET, CT, among others) have significantly improved clinical localisation of lesions of the central nervous system (CNS) before surgery, making possible for neurosurgeons to plan and navigate away from functional brain locations when removing tumours, such as gliomas. However, neuronavigation in the surgical management of brain tumours remains a significant challenge, due to the inability to maintain accurate spatial information of pathological and healthy locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…This same group used has also used this LCTF-based HSI system for PpIX detection in pediatric tumors (Schwake et al, 2019), and has demonstrated more sensitive detection of autofluorescence and PpIX spectral features such as the 620 and 634 nm states in ex vivo samples from 128 patients with HGG and LGG (Black et al, 2021), and implemented new phantom recommendations for HSI in 5-ALA-PpIX FGS (Walke et al, 2023). Another use of HSI that is being explored by an ongoing European collaborative is centered on a system that may ultimately be capable of mapping, monitoring and quantifying biomolecules of interest; it has been engineered to be handheld and user-friendly, and apply artificial intelligence-based methods for the reconstruction of spectrally-resolved images (Giannoni et al, 2023). Such efforts are positioning HSI technologies in a way that may potentially improve diagnostic performance across the full surgical field of view in 5-ALA-PpIX FGS.…”
Section: Discussionmentioning
confidence: 99%
“…This same group used has also used this LCTF-based HSI system for PpIX detection in pediatric tumors (Schwake et al, 2019), and has demonstrated more sensitive detection of autofluorescence and PpIX spectral features such as the 620 and 634 nm states in ex vivo samples from 128 patients with HGG and LGG (Black et al, 2021), and implemented new phantom recommendations for HSI in 5-ALA-PpIX FGS (Walke et al, 2023). Another use of HSI that is being explored by an ongoing European collaborative is centered on a system that may ultimately be capable of mapping, monitoring and quantifying biomolecules of interest; it has been engineered to be handheld and user-friendly, and apply artificial intelligence-based methods for the reconstruction of spectrally-resolved images (Giannoni et al, 2023). Such efforts are positioning HSI technologies in a way that may potentially improve diagnostic performance across the full surgical field of view in 5-ALA-PpIX FGS.…”
Section: Discussionmentioning
confidence: 99%